Amount and chain length of polyphosphates in Escherichia coli depend on cell growth conditions. - Rao, N N (1985)
Anaerobiosis induced an accumulation of polyphosphates (poly Pi) in a phosphate-rich medium by an alkaline-phosphatase constitutive mutant of Escherichia coli. The total poly Pi content was maximum at around 6 h of anaerobic growth. Both trichloroacetic acid- and NaOH-soluble poly Pi were found to be present. The acid-soluble fraction consisted mainly of a linear polymer of about 20 +/- 5 phosphate units, whereas the alkali-extractable poly Pi fraction contained at least four molecular species of higher chain length as determined by gel filtration. The majority of poly Pi extracted at 6 h had lower chain lengths than those extracted from cells incubated for 24 h. In vivo 31P nuclear magnetic resonance spectra of E. coli cells as a function of growth conditions were consistent with the in vitro extract results.